To the study of macrophytobenthos of coastal waters of Karadzhinsky Plot on Tarkhankut Peninsula (Crimea, Black Sea) - Sadogurskiy, S. Ye. (Marine Biological Journal, 2020)
Composition and distribution of seaweeds in coastal waters of the Karadzhinskaya Bay, adjacent to the southern cluster of a specially protected natural area “Tarkhankut” Nature Park (Crimea, Tarkhankut Peninsula, Black Sea), are described and discussed. Peculiarities of the coastal zone geomorphology determine structural features of macrophytobenthos and its intermediate position in relation to macrophytobentos of adjacent abrasive and accumulative coasts. Totally 57 species of seaweeds were identified (Chlorophyta – 12, Ochrophyta (сl. Phaeophyceae) – 12, Rhodophyta – 33); 21 of them occur in pseudolittoral, and 56 – in sublittoral. Biomass ranges from 0.5 kg per m² in pseudolittoral to 4.5 kg per m² in sublittoral. Nature and quantity of benthic vegetation, flora composition, and ratio of main ecological-floristic groups of macrophytobenthos are generally characteristic for the Tarkhankut-Sevastopol hydrobotanical region of the Black Sea. A rare fraction of flora includes 14 taxa listed in nature conservation lists of various ranks. The biotope subjects to special protection according to the EU Habitats Directive (Directive 92/43/EEC). The territorial-aquatic complex is important both from nature protection and recreation points of view. Its conservation will contribute to structural and functional integrity of Black Sea coastal zone ecosystem.